CAMERON, Maxwell A., 2013, Strong Constitutions: Social-Cognitive Origins of the Separation of Powers, Nueva York, Oxford University Press. 255 pp. - Ilizarbe Pizarro, Carmen (2015)
Se reseñó el libro: Strong Constitutions: Social-Cognitive Origins of the Separation of Powers.